O16 Ethnic variations in sexual risk behaviour, sexual health service use and unmet need during the first year of the COVID-19 pandemic: an analysis of population-based survey and surveillance data. (16th June 2022) - Ratna, Natasha; Dema, Emily; Conolly, Anne; Riddell, Miss Julie; Willis, Malachi; Pérez, Raquel Bosó; Copas, Andrew; Gibbs, Jo; Clifton, Soazig; Unemo, Magnus; Migchelsen, Stephanie J; Sonubi, Tamilore; et al.
Abstract : Introduction: Prior to the COVID-19 pandemic, STIs disproportionately affected some Black communities. We examined ethnic inequalities in sexual health during the pandemic. Methods: Analyses were restricted to England residents aged 18–59. We included 5, 240 sexually-experienced participants from Natsal-COVID survey Wave 2 (quasi-representative web panel survey) reporting one-year outcomes from March 2020-April 2021. We estimated weighted proportions and adjusted odds ratios (AORs) between ethnicity and sexual risk behaviour (condomless sex with new partner on first occasion), sexual health service (SHS) use, and unmet need (trying but failing to access SHS). Using GUMCAD national surveillance data from before (March 2019-March 2020) and during (March 2020-March 2021) the pandemic, we compared proportional differences in rates of STI tests and diagnoses by ethnicity. Results: Compared to Natsal-COVID participants of White ethnicity, sexual risk behaviour (8%) was higher among participants of Mixed/Other (22%, AOR:2.26 [95% CI 1.08-4.73]) and Asian (15%, 1.58 [1.07-2.35]); SHS use (5%) was higher in Black (20%, 3.04 [1.75-5.28]) and Mixed/Other (20%, 2.64 [1.35-5.14]); and unmet need (2%) was higher in Black (11%, 5.01 [2.26-11.09]) and Asian (5%, 2.33 [1.11-4.90]) ethnicity. In GUMCAD, among people attending SHS, we observed similar reductions of around 50% in testing and diagnoses during the pandemic across different ethnic groups, although the greatest reduction was in people of Asian ethnicity (56% and 52% respectively). Discussion: Two independent national data sources showed sexual health inequalities persisted during the first year of the pandemic with evidence of more unmet need among minority ethnicities, but further work is needed to assess whether these worsened.